PENGARUH PERILAKU DAN KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN DAN KOTA DI PROVINSI KALIMANTAN SELATAN - Murdiansyah Herman (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2018)
Analyze the influence of behavior on the quality of public services, behavior on performance, and performance on the quality of public services at the Population and Civil Registry Service in the Province of South Kalimantan. This research uses quantitative methods which can be interpreted as research methods based on positivist philosophy. The design of this study was observational with a cross sectional approach. The sample of this study was 325 people and spread in 13 cities and districts in the Province of South Kalimantan. The results of this study are that employee behavior has a significantly positive effect on employee performance. Employee behavior significantly influences the Quality of Public Services. Employee performance does not significantly influence the Quality of Public Services.